Current Understanding of Host Genetics of Otitis Media - Geng, Ruishuang; Wang, Qingzhu; Chen, Eileen; Zheng, Qing Yin (Frontiers in Genetics, 2020)
The pathogenesis of otitis media (OM), an inflammatory disease of the middle ear (ME), involves interplay between many different factors, including the pathogenicity of infectious pathogens, host immunological status, environmental factors, and genetic predisposition, which is known to be a key determinant of OM susceptibility. Animal models and human genetics studies have identified many genes and gene variants associated with OM susceptibility: genes that encode components of multiple signaling pathways involved in host immunity and inflammatory responses of the ME mucosa; genes involved in cellular function, such as mucociliary transport, mucin production, and mucous cell metaplasia; and genes that are essential for Eustachian tube (ET) development, ME cavitation, and homeostasis. Since our last review, several new mouse models with mutations in genes such as CCL3, IL-17A, and Nisch have been reported. Moreover, genetic variants and polymorphisms in several genes, including FNDC1, FUT2, A2ML1, TGIF1, CD44, and IL1-RA variable number tandem repeat (VNTR) allele 2, have been identified as being significantly associated with OM. In this review, we focus on the current understanding of the role of host genetics in OM, including recent discoveries and future research prospects. Further studies on the genes identified thus far and the discovery of new genes using advanced technologies such as gene editing, next generation sequencing, and genome-wide association studies, will advance our understanding of the molecular mechanism underlying the pathogenesis of OM and provide new avenues for early screening and developing effective preventative and therapeutic strategies to treat OM.